The relationship between core stability and rupture of anterior cruciate ligament in soccer players - Masomeh Taghikhani; Nasrin Naseri; Sayed Sadredin Shojaedin (Vesnu Publications, 2012)
Introduction: ACL Tearing is one of the most common injuries among athletes. In previous studies, the association between ACL injury and factors such as gender, age, type of sport activity, level of sexual hormones and joint laxity has been evaluated. Although diminished endurance of the lower trunk and core body muscles seems to play a potential role in ACL injury, these factors have not been evaluated adequately. The main objective of the present study is to assess the relationship between core stability and rupture of anterior cruciate ligament in soccer players. Materials and Methods: In this cross-sectional study, the endurance of trunk extensors, trunk flexors and trunk lateral flexors were measured in 30 professional soccer players among whom 15 persons had unilateral torn ACL (mean age = 23.4) and the remaining had normal ACL (mean age = 21.7) .We performed the McGill and Biering-Sorensen tests to measure the endurance of these muscles in both groups utilizing a digital chronometer. Results: The endurance of trunk extensors, trunk flexors and trunk lateral flexors were statistically lower in soccer players with torn ACL compared to the soccer players with normal functioning ACL (P < 0.05). Conclusion: Diminished endurance of the trunk muscles is a possible factor that increases the chance of ACL rupture in soccer players. This certainly has to be proved with prospective comparative studies and, if it is the case, then increasing the endurance of these muscles can possibly decrease the risk of ACL injury. Keywords: Core stability, Lower trunk muscles, Anterior cruciate ligament, Soccer players